A Solution Proposal to Vehicle Routing Problem with Integer Linear Programming: A Distributor Company Sample - Tüzemen, Adem; YILDIZ, ÇAĞDAŞ (International Journal of Contemporary Economics and Administrative Sciences, 2019)
It was aimed to minimize the total distance of the routes under the capacity constraint of the routes that a distributor company has drawn in the direction of the demands. To this end, a route to Gebze-based steel production and distribution was drawn up to meet all the demands of a fabrication plant. In order to determine the minimum total distance routes, the solution recommendation by adapting the Capacity Constrained Vehicle Routing Problem (CVRP) which is one of the basic route problems using Branch and Cut algorithm of 0-1 Integer Linear Programming (ILP) was introduced. Distances between the nodes that make up the route are measured via Google Maps. Optimal solutions were obtained by using LINDO computer software to solve the problem. .